Econometrica (JSTOR)
The journal publishes original articles in all branches of economics - theoretical and empirical, abstract and applied, providing wide-ranging coverage across the subject area. It promotes studies that aim at the unification of the theoretical-quantitative and the empirical-quantitative approach to economic problems and that are penetrated by constructive and rigorous thinking.
Keywords: Business, Business & Economics, Economics, Mathematics, Science & Mathematics